Physiological responses of native and crossbred sheep to climatic stress under semi-arid conditions* - ASHUTOSH, ASHUTOSH; DHANDA, O P; KUNOU, R L (The Indian Journal of Animal Sciences, 2014)
Rectal temperature, pulse rate and respiration rate in native (Chokla) lmd Avivastra (Chokla x Rambouillet) sheep were investigated during different seasons kept under semi-arid conditions after following standard procedures. The results revealed that there exists a significant difference in rectal temprature in animals of both the breeds between seasons. However, the rectal temperature in native and crossbred animals did not differ significantly in summer season. Sigmficant diurnal variation was observed in crossbreds in all the seasons’ except spring. A significantly higher(P<0.05) respiration rate was observed in crossbred sheep in winter, spring and summer seasons in comparison to the natives without any significant difference in the rainy season. Higher respiration rate was found in the afternoon in native as well as in crossbreds in all the seasons in comparison to that ofmoming hours. Pulse rate was significantly higher in native animals in summer and winter, However, the trend got reverse during spring season. It was thus concluded that native as well as crossbred sheep are equally efficient in thermoregulatory mechanism under semiarid conditions.